Unabated Adenovirus Replication following Activation of the cGAS/STING-Dependent Antiviral Response in Human Cells - Lam, Eric (J Virol, 2014)
The cGAS/STING DNA sensing complex has recently been established as a predominant pathogen recognition receptor (PRR) for DNA-directed type I interferon (IFN) innate immune activation. Using replication-defective adenovirus vectors and replication-competent wild-type adenovirus, we have modeled the influence of the cGAS/STING cascade in permissive human cell lines (A549, HeLa, ARPE19, and THP1). Wild-type adenovirus induced efficient early activation of the cGAS/STING cascade in a cell-specific manner. In all responsive cell lines, cGAS/STING short hairpin RNA (shRNA) knockdown resulted in a loss of TBK1 and interferon response factor 3 (IRF3) activation, a lack of beta interferon transcript induction, loss of interferon-dependent STAT1 activation, and diminished induction of interferon-stimulated genes (ISGs). Adenoviruses that infect through the coxsackievirus-adenovirus receptor (CAR) (Ad2 and Ad5) and the CD46 (Ad35) and desmoglein-2 (Ad7) viral receptors all induce the cGAS/STING/TBK1/IRF3 cascade. The magnitude of the IRF3/IFN/ISG antiviral response was strongly influenced by serotype, with Ad35>Ad7>Ad2. For each serotype, no enhancement of viral DNA replication or virus production occurred in cGAS or STING shRNA-targeted cell line pools. We found no replication advantage in permissive cell lines that do not trigger the cGAS/STING cascade following infection. The cGAS/STING/TBK1/IRF3 cascade was not a direct target of viral antihost strategies, and we found no evidence that Ad stimulation of the cGAS/STING DNA response had an impact on viral replication efficiency. IMPORTANCE This study shows for the first time that the cGAS DNA sensor directs a dominant IRF3/IFN/ISG antiviral response to adenovirus in human cell lines. Activation of cGAS occurs with viruses that infect through different high-affinity receptors (CAR, CD46, and desmoglein-2), and the magnitude of the cGAS/STING DNA response cascade is influenced by serotype-specific functions. Furthermore, activation of the cGAS cascade occurred in a cell-specific manner. Activation of the cGAS/STING response did not impact viral replication, and viral immune evasion strategies did not target the cGAS/STING/TBK1/IRF3 cascade. These studies provide novel insight into the early innate recognition response to adenovirus.